Estimating Available Bandwidth Using Multiple Overloading Streams - Zhang, Minjian; Luo, Chong; Li, Jiang (Proceedings of IEEE ICC'06, 2006)
Available bandwidth measurement is essential to applications running on the best-effort Internet. In this paper, we propose an available bandwidth measurement technique named MoSeab. The idea behind MoSeab is a direct probing technique based on a statistical model for network data transmissions. Differing from the other direct probing techniques, MoSeab does not require any a priori knowledge of network path. It has proven valid even when there are multiple bottlenecks. Simulation and real Internet experiments demonstrate the accuracy and robustness of MoSeab, and show its advantages over Spruce, PathChirp, and IGI. Moreover, its probing traffic control mechanism makes MoSeab a non-intrusive solution suitable to be integrated into various network applications.